FORM FACTORS AND DENSITY DISTRIBUTIONS OF PROTONS AND NEUTRONS IN 7Li AND 7Be - A.D. Duisenbay; N.ZH. Takibayev; V.S. Vasilevsky; V.O. Kurmangaliyeva; E.M. Akzhigitova (Academic Scientific Journal of Computer Science, 2019)
Form factors and density distribution of protons and neutrons in 7Li and 7Be are investigated within a microscopic two-cluster model. The model correctly treat the Pauli principle and make use of the oscillator basis to expand wave function of two-cluster system. Dynamics of two-cluster system is totally governed by a semirealistic nucleon-nucleon potential. We demonstrate that the model used correctly reproduces form factors for the ground state of 7Li and 7Be.